Prediction of the Higgs and Top Quark Masses by Discrete Dimensions Revisited - Dat, Nguyen Van; Ai Viet, Nguyen; Du, Pham Tien (VNU Journal of Science: Mathematics - Physics, 2020)
A new metric structure of the discretized Kaluza-Klein theory can give us new knowledge about extra-dimension . It can provide the new predictions of the top quark and Higgs mass that studied by Viet [15 , 16] in another model. Compare the results of two approaches we can see that the new model is more agreement with experimental data.